Chemical modification by peroxynitrite enhances TLR4 activation of the grass pollen allergen Phl p 5 - Reinmuth-Selzle, Kathrin; Bellinghausen, Iris; Leifke, Anna Lena; Backes, Anna T.; Bothen, Nadine; Ziegler, Kira; Weller, Michael G.; Saloga, Joachim; Schuppan, Detlef; Lucas, Kurt; Pöschl, Ulrich; Fröhlich-Nowoisky, Janine (Frontiers in Allergy, 2023)
The chemical modification of aeroallergens by reactive oxygen and nitrogen species (ROS/RNS) may contribute to the growing prevalence of respiratory allergies in industrialized countries. Post-translational modifications can alter the immunological properties of proteins, but the underlying mechanisms and effects are not well understood. In this study, we investigate the Toll-like receptor 4 (TLR4) activation of the major birch and grass pollen allergens Bet v 1 and Phl p 5 and how the physiological oxidant peroxynitrite (ONOO-) changes the TLR4 activation through protein nitration and the formation of protein dimers and higher oligomers. Of the two allergens, Bet v 1 exhibited no TLR4 activation, but we found TLR4 activation of Phl p 5, which increased after modification with ONOO- and may play a role in the sensitization against this grass pollen allergen. We attribute the TLR4 activation mainly to the two-domain structure of Phl p 5 which may promote TLR4 dimerization and activation. The enhanced TLR4 signaling of the modified allergen indicates that the ONOO–induced modifications affect relevant protein-receptor interactions. This may lead to increased sensitization to the grass pollen allergen and thus contribute to the increasing prevalence of allergies in the Anthropocene, the present era of globally pervasive anthropogenic influence on the environment.